Automated Machine-Tractor Unit for Grass Mowing - Z. A. Godzhaev; S. A. Vasilyev; S. A. Mishin; E. V. Ruzanov (Сельскохозяйственные машины и технологии, 2025)
Recent advancements in robotics and automation have significantly contributed to the progress of precision agriculture. This study presents the development of an automated machine-tractor unit (MTU) designed for grass mowing, incorporating universal mechatronic control modules. (Research purpose) The purpose of this research is to design a functional and technological scheme for an automated machine-tractor unit and to develop universal mechatronic modules that can be mounted onto the mechanical control elements typically operated by a human driver. These modules are intended to enable the automated execution of the grass mowing process. (Materials and methods) A functional and technological scheme of the machine-tractor unit was developed. The unit consists of a remote control system, a tractor, an access control and management system (ACMS), and a technological implement. The methodology for the automatic control of the machine-tractor unit in an agro-landscape was described. A theoretical justification was provided for the design and technological parameters of the universal mechatronic modules used to control the clutch and braking systems. Calculations were conducted for the mechatronic module mechanism, including the determination of the screw drive gear ratio, screw travel, and nut displacement speed. A functional relationship was established between the pedal stroke velocity (change in pedal angle) and the nut displacement speed in the mechatronic actuation module. Control software for the universal mechatronic modules was developed using a programming language suitable for the selected controller. (Results and discussion) Automatic control of the machine-tractor unit was successfully implemented in an agro-landscape setting using a remote control panel, an LTZ-120B wheeled tractor, and a KRN-2.4 rotary mower. Field tests were conducted to evaluate the interaction between the control software and the hardware components of the universal mechatronic control modules. Comparative experimental studies were performed during straight-line mowing operations to evaluate the system performance under both manual control (with an operator) and automated control (using mechatronic actuators). (Conclusions) Preliminary tests of the automated agricultural machine-tractor unit demonstrated that its operational performance indicators remained within acceptable limits during mower-assisted operations. Specifically, the system achieved a productivity rate of 3.56 hectares per hour of effective operation, maintained a working speed of 10 ± 0.3 kilometers per hour, and ensured a grass cutting height of 8 ± 1 centimeters.